Photobiomodulation versus corticosteroid in the management of erosive oral lichen planus: a randomized controlled clinical trial - Reem Kamal Mohamed; Naguiba Mahmoud Elsayed; Sabah Abdelhady Mahmoud; Yasmine Youssri Gaweesh (BMC, 2024)
Abstract Background Oral lichen planus (OLP) is a chronic illness of immune origin that is typically treated with corticosteroids as a gold standard therapy. Photobiomodulation (PBM) may represent an alternative remedy that has the potential to treat a variety of pathological conditions by alleviating pain, reducing inflammation, and promoting tissue healing without the drawbacks of steroid therapies. Thus, the aim of the current study was to compare the effect of photobiomodulation to topical 0.1% triamcinolone acetonide on erosive oral lichen planus. Methods This randomized controlled clinical trial involved 44 patients complaining of erosive oral lichen planus. Patients were assigned to one of two groups: control group (n = 22) received 0.1% topical triamcinolone acetonide three times daily with miconazole oral gel once daily for 4 weeks, and photobiomodulation group (n = 22) received laser therapy by 980 nm diode laser utilizing output power 300 mW twice weekly for 5 weeks (a total of 10 sessions). The evaluation of patients was performed at baseline, 6 weeks, and 12 weeks postoperatively in terms of pain, clinical scores, and biochemical evaluation of salivary malondialdehyde levels. All recorded data were analyzed using Mann-Whitney test to compare the two studied groups regarding pain, lesion size, and salivary levels of malondialdehyde. Friedman test, followed by post hoc test, was used for comparison of the data within the same group along the 3 periods at baseline, 6 weeks, and 12 weeks. Results Both groups showed significant improvement in pain and clinical scores, with no statistical difference between them. Moreover, there was a significant improvement in salivary malondialdehyde levels for both groups, with no significant difference between them. Conclusions Photobiomodulation could be a promising therapeutic modality for management of erosive oral lichen planus without the side effects of steroid therapy. The salivary malondialdehyde level could be used as a biomarker to evaluate the disease severity and its response to the treatment. Trial registration The study has been registered at ClinicalTrials.gov (NCT05951361) (19/07/2023).